2020
DOI: 10.3892/ol.2020.11872
|View full text |Cite
|
Sign up to set email alerts
|

Functions of mammalian SIRT4 in cellular metabolism and research progress in human cancer (Review)

Abstract: Sirtuins are mammalian homologs of yeast silent information regulator two (SIRT) and are a highly conserved family of proteins, which act as nicotinamide adenine dinucleotide (NAD + )-dependent histone deacetylases. The seven sirtuins (SIRT1-7) share a conserved catalytic core domain; however, they have different enzyme activities, biological functions, and subcellular localizations. Among them, mitochondrial SIRT4 possesses ADP-ribosyltransferase, NAD + -dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 123 publications
(178 reference statements)
3
13
0
Order By: Relevance
“…Bioinformatics analysis revealed that SIRT4 might be a direct target of miR‐130b‐5p. SIRT4, which resides mitochondria and plays a significant role in cellular metabolic processes 26 . EX‐527, as a SIRT1‐selective inhibitor, relieve hepatic fibrosis by up‐regulating SIRT4 expression 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioinformatics analysis revealed that SIRT4 might be a direct target of miR‐130b‐5p. SIRT4, which resides mitochondria and plays a significant role in cellular metabolic processes 26 . EX‐527, as a SIRT1‐selective inhibitor, relieve hepatic fibrosis by up‐regulating SIRT4 expression 14 .…”
Section: Discussionmentioning
confidence: 99%
“…SIRT4, which resides mitochondria and plays a significant role in cellular metabolic processes. 26 EX-527, as a SIRT1-selective inhibitor, relieve hepatic fibrosis by up-regulating SIRT4 expression. 14 A previous study indicated that SIRT4 silencing in tumour-associated macrophages promotes HCC development.…”
Section: Discussionmentioning
confidence: 99%
“…The use of a transgenic mouse model for cancer xenotransplantation has confirmed that a lack of SIRT4 can accelerate the progression of cancer cell death in various cancers by regulating glutamine metabolism in the mitochondria or the mammalian target of rapamycin (mTOR) pathways (Csibi et al, 2013;Jeong et al, 2013). However, its role in breast cancer and OC seems to stand at the opposite end of the spectrum (Sun et al, 2019b;Wang et al, 2020). Du et al (2020) have highlighted that SIRT4 negatively regulates SIRT1 expression by suppressing glutamine metabolism in mammary tumorigenesis, which implies the presence of competition functions within the sirtuin family.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, SIRT4 has been reported to enhance E-cadherin and inhibit EMT, thereby decreasing migration and the invasion ability in gastric and colorectal cancer cells[ 70 , 71 ]. Furthermore, Hu et al [ 72 ] showed that overexpression of SIRT4 induced G1 cell cycle arrest through the inhibition of the phosphorylated extracellular signal-regulated kinases cyclin D and cyclin E. In addition, several studies have revealed that a low SIRT4 expression was significantly correlated with a poor prognosis in patients with various cancers[ 73 ].…”
Section: Sirt4mentioning
confidence: 99%